Development of a customised data management system for a COVID-19-adapted colorectal cancer pathway. Issue 1 (9th July 2021) - Miller, Janice; Gunn, Frances; Dunlop, Malcolm G; Din, Farhat VN; Maeda, Yasuko
Abstract : Objectives: A customised data management system was required for a rapidly implemented COVID-19-adapted colorectal cancer pathway in order to mitigate the risks of delayed and missed diagnoses during the pandemic. We assessed its performance and robustness. Methods: A system was developed using Microsoft Excel (2007) to retain the spreadsheets' intuitiveness of direct data entry. Visual Basic for Applications (VBA) was used to construct a user-friendly interface to enhance efficiency of data entry and segregate the data for operational tasks. Results: Large data segregation was possible using VBA macros. Data validation and conditional formatting minimised data entry errors. Computation by the COUNT function facilitated live data monitoring. Conclusion: It is possible to rapidly implement a makeshift database system with clinicians' regular input. Large-volume data management using a spreadsheet system is possible with appropriate data definition and VBA-programmed data segregation. The described concept is applicable to any data management system construction requiring speed and flexibility in a resource-limited situation.